RETRACTED: Improvement of the design of a vertical steel tank for oil and petroleum products - Saveleva N.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001